+@ UCja3 úim/2i2KTQ`2HH2/2b bvbi K2bHBMû B`2b .+@ UCja3 8úim/2i2KTQ`2HH2/2b bvbi K2bHBMû B`2b

  • View
    222

  • Download
    0

Embed Size (px)

Text of +@ UCja3 úim/2i2KTQ`2HH2/2b bvbi K2bHBMû B`2b .+@ UCja3 8úim/2i2KTQ`2HH2/2b bvbi K2bHBMû B`2b

  • ds(t)dt

    + s(t) = K e(t)

    K

    e(t)L E(p) s(t) L S(p)

    p S(p) + S(p) = K E(p)

    H(p) =S(p)

    E(p)=

    K

    1+ pK

    1+ p

    s(t)e(t) = E0 H(t)

    s(t)

    ds(t)dt

    + s(t) = K e(t)

    s(t) = K E0 1 et

  • S(p) = H(p) E(p)S(p) =

    K

    1+ p E0p

    e(t)L E0

    p

    S(p) =A

    p+

    B

    1+ pS(p) =

    K E0p

    K E0 1+ p

    K E0p

    L1 K E0 H(t)

    K E0 1+ p

    L1 K E0 et

    H(t)

    s(t) = K E0 1 et

    H(t)

    t s(t) = p0p S(p)

    t s(t) = p0(p K

    1+ p E0p

    )

    t s(t) = K E0K E0 ts(t)

    t = 0

    t0s(t) =

    pp S(p)

    t0s(t) =

    p(p K

    1+ p E0p

    )

    t0s(t) = 0

    s(t)t = 0

    f(t) F(p)

  • L

    (f(t)

    )= p F(p) f(0+)

    L

    (f(t)

    )= p F(p)

    s(t) =s(t)

    s = K E00 95 K E0

    0 63 K E0

    3

    T5 = 3 1

    312

    323

    33

    t0s(t) =

    t0s(t)

    =pp

    2 S(p) =p

    (p2 K

    1+ p E0p

    )=

    K

    E0

    K E0

    =s

    K E0

  • T55

    s() s(T5 )s() = 0 05

    K E0 K E0 (1 e

    T5

    )K E0 = 0 05

    eT5

    = 0 05

    T5 3

    K

    K

    2

    e(t) = (t)

    S(p) = H1(p) =K

    1+ p s(t) =K

    e

    t

    K a

    a

    e(t) = a t H(t)

    S(p) = H1(p) E(p) = K1+ p

    a

    p2

    s(t) = K a t

    1 e t

    K a( 0)

  • a2 2 s(t)

    2+ a1 s(t) + a0 s(t) = b0 e(t)

    1

    2n

    2 s(t)2

    +2 n

    s(t) + s(t) = K e(t)n > 0 rad s

    1

    > 0 :

    K

    1

    2n

    2 s(t)2

    +1

    Q n s(t)

    + s(t) = K e(t)n > 0

    Q =1

    2 K

    e(t) E(p) s(t) L S(p)

    p2

    2n S(p) + 2

    n p S(p) + S(p) = K E(p)(

    p2

    2n+

    2 n

    p+ 1) S(p) = K E(p)

    H(p) =S(p)

    E(p)=

    K

    1+2 n

    p+ p2

    2n

    K

    1+2 n

    p+ p2

    2n

    =4 22n

    4

    2n=

    4

    2n (2 1)

    > 1 > 0

    r1 = n (

    2 1

    )r2 = n

    (+

    2 1

    )

  • 1 = 1

    r1=

    1

    n (

    2 1

    ) 2 = 1r2

    = 1

    n (+

    2 1

    )

    =1 + 2

    2 1 2 n =1

    1 2

    H(p) =K

    (1+ 1 p) (1+ 2 p)

    = 1 = 0

    r = n

    H(p) =K(

    1+p

    n

    )2 = K(1+ p)2

    0 < < 1 < 0

    r1 = n ( j

    1 2

    )r2 = n

    (+ j

    1 2

    )

    H(p) =K

    1+2 n

    p+ p2

    2n

    e(t) = E0 H(t) H(t)

    S(t) =K

    1+2 n

    p+ p2

    2n

    E0p

    > 0 n > 0

    t s(t) = p0p S(p) = p0

    p K

    1+2 n

    p+ p2

    2n

    E0p

    t s(t) = K E0

  • K

    t0s(t) =

    pp S(p) = p

    p K

    1+2 n

    p+ p2

    2n

    E0p

    t0s(t) = 0

    t0s(t) =

    pp p S(p) = p

    p2 K

    1+2 n

    p+ p2

    2n

    E0p

    t0s(t) = 0

    n > 0 n > 0

    > 1

    S(t) =K

    (1+ 1 p) (1+ 2 p) E0p

    S(p) = K E0 (1

    p

    211 2

    11+ 1 p

    222 1

    11+ 2 p

    )

    s(t) = K E0

    1 1

    1 2 e

    t

    1 2

    2 1 e

    t

    2 H(t)

    > 1 =1 + 2

    2 1 2n

    z = 1

    S(t) =K

    (1+ p)2 E0p

    S(p) = K E0 (1

    p

    (1+ p)2

    (1+ p))

  • t

    K E00 95 K E0

    > 1

    > 1

    = 1

    s(t) = K E0 1 t+

    e

    t

    H(t)

    n

    s(t) = K (1 (1+n t) ent) H(t)0 < < 1

    S(p) =K

    1+2 n

    p+ p2

    2n

    E0p

    s(t) = K E0(1

    11 2

    eznt (n

    1 2 t+

    ))H(t) =

    p

    p = n 1 2

    s(t) = K E0(1

    11 2

    eznt (p t+))H(t)

    s(t) = K E0(1

    ((p t) +

    1 2 (p t)

    ) ent

    )H(t)

  • t

    K E00 95 K E01 05 K E0

    0 < < 1

    0 < < 1

    = 1

    Tpm =Tp

    2

    Tp

    t

    K E00 95 K E01 05 K E0

    0 < < 1

    Tp =2

    n 1 2

    p = n 1 2

    Tpm =Tp

    2=

    n

    1 2

    D1 = e

    1 2

  • D1

    D2

    D3

    D4

    D5

    D6

    D7

    D8

    D1

    D2

    D3D4

    t

    s

    +5

    5

    Tr0 7 Tr1

    = 1

    0 7T5 n

    > 0 7

    > 0 7

    0 7 = 1

    = 0 7 D1 = e

    1 2 = 0 05

    T5

  • z

    Tr n

    H(p) =K

    1+ 2znp+p2

    2n

    t

    s

    e(t) = E0 H(t)

    s(t) = K E0 t H(t)

    s(t)= K e(t)

    s(t) =

    +0

    K e(u) u

    H(p) =S(p)

    E(p)=

    K

    pK

    p

    s(t) = K e(t)

    H(p) =S(p)

    E(p)= K p K p

  • s(t) = e(t )

    H(p) =S(p)

    E(p)= ep ep

    +

    E(p)T(p)

    (p) S(p)

    BF(p) =S(p)

    E(p)=

    T(p)

    1+ T(p)

    T(p) =Ko

    1+ o pKo o

    BF(p) =S(p)

    E(p)=

    Ko

    1+ o p1+

    Ko

    1+ o p=

    Ko

    1+Ko + o p

    BF(p) =

    Ko

    1+Ko

    1+o

    1+Ko p

    Kf =Ko

    1+Ko

    f =o

    1+Ko

    Ko

  • e(t) = E0 H(t)

    t s(t) = p0p S(p) = p0(p Kf

    1+ f p E0p

    )= Kf E0

    t s(t) =Ko

    1+Ko E0

    i

    i =t (t) = p0p (p) = p0 (p (E(p) S(p)))

    i = (

    (1

    Ko

    1+Ko

    ) E0 = 1

    1+Ko E0

    Ko

    T(p) =Ko

    1+2 on0

    p+ p2

    2n0

    Ko o no

    BF(p) =

    Ko

    1+Ko

    1+20

    (1+Ko) no p+p2

    (1+Ko) 2no

    Kf =K0

    1+Ko

    nf = no 1+Ko > no

    f =o1+Ko

    < o

    1 Ko

    H(p) =K

    1+ a1 p+ a2 p2 + + an pn

  • H(p) =S(p)

    E(p)=

    1

    (1+ p) (1+

    p

    6

    )(1+

    p

    20

    )

    s(t) = 125

    19 et 1

    57 e20t + 1

    3 e5t

    e20t

    et e5t

    H2(p) =1

    (1+ p) (1+

    p

    6

    ) H1(p) = 1(1+ p)

    t

    s

    H(p) H2(p)

    t

    s

    H(p) H1(p)

  • H(p) = K 1+ a p1+ b1 p+ b2 p2

    H(p) = K (

    1

    1+ b1 p+ b2 p2 + a p

    1+ b1 p+ b2 p2)

    a

    S(p) = K (

    1

    1+ b1 p+ b2 p2 1

    p+ a p

    1+ b1 p+ b2 p2 1

    p

    )

    s1(t) =1

    (1

    1+ b1 p+ b2 p2 1

    p

    )

    s(t) = K (s1(t) + a s1(t)

    )

    t s(t) = p0p S(p)

    =p0

    (p K

    (1

    1+ b1 p+ b2 p2 1

    p+ a p

    1+ b1 p+ b2 p2 1

    p

    ))= K

    s1(t)

    0 5 s1(t)

    s(t)

    t

    s

    H(p) =1+ 0 5 p1+ p+ p2

    =1

    1+ p+ p2+

    0 5 p1+ p+ p2

    s(t) = s1(t) + 0 5 s1(t)

  • H(p) =1 0 5 p1+ p+ p2

    =1

    1+ p+ p2+

    0 5 p1+ p+ p2

    s(t)

    s1(t)

    0 5 s1(t)

    s(t)

    t

    s

    ts

    H(p) =K

    (1+ p) (1 p) > 0

    e(t) = E0 H(t)

    S(p) =K

    (1+ p) (1 p) E0p

    S(p) = K E0 (1

    p

    2 (1+ p) +

    2 (1 p))

    s(t) = K E0 1 1

    2

    e t + e t

    H(t)

  • t

    s

    H(p) =1

    1 p+ 10 p2

  • s(t)+ 10 s(t) = 3 u(t)

    u(t) = K (e(t) s(t))

    +

    E(p) (p) U(p) S(p)

    K i 5

    e(t) = 2 H(t) 5

    +

    E(p)A

    (p)F(p)

    U(p) S(p)

    A A = 10

    F(p)

    e(t) = E0H(t) E0 = 5

    0 08 s

    F(p)F(p)

    F(p) =K

    1+ p

    T(p) =S(p)

    E(p)K A

    T(p) =G

    1+ T pG T

    e(t) = E0H(t) E(p) e(t) S(p)G

  • s(t) T

    s(t) s(t)

    A = 10 K F(p)

    A

    t

    s

    e(t)

    200mm 1200mm

    y0y0

    y(t)

    yc(t)

  • i = 0

    i =t (y(t) yc(t))

    T5 5 s

    d1 < 5

    d1 =ymax y

    y

    Hm(p) =Y(p)

    M(p)=

    Km

    1+ a1 p+ a2 p2

    qm(t) =m(t)

    a1 = 0 7 s a2 = 45 9 103 s2 Km = 2mkg1

    qm(t) ur(t)

    Hd(p) =Qm(p)

    Ur(p)= Kd = 0 2 kg s

    1 V1

  • um(t) y(t)(t) = uc(t) um(t) A

    uc(t) yc(t)

    Hc(p) =Um(p)

    Y(p)= Kc = 10V m

    1

    Uc(p) = G Yc(p)

    GYc(p)

    +

    Uc(p)A

    (p)Hd(p)

    Ur(p)Hv(p)

    Qm(p)Hm(p)

    M(p) Y(p)

    Hc(p)

    Um(p)

    G = Kc Hv(p) =1

    p

    HBO(p) =Um(p)

    (p)

    HBO(p) HBO(p) =K

    p (1+ 2

    0 p+ p

    2

    20

    )K 0

    HBF(p) =Y(p)

    Yc(p)

    HBF(p) =KBF

    1+ b1 p+ b2 p2 + b3 p3